Extreme alignment: Understanding the costs and risks of the assessment regime and identifying potential solutions - Rutt, Rebecca (Improving University Science Teaching and Learning, 2023)
This project reports presents my pedagogical research associated with the University of Copenhagen ‘Teaching and Learning in Higher Education Programme’ (Universitetspædagogikum). It draws from my experience as Course Responsible of the MSc course ‘Research Planning’ during the period end-August 2015 – end-October 2015. The report will present a case of what I claim to be ‘extreme alignment’. It begins by explaining the notion of alignment in teaching, including the role of assessment, and continues with an introduction to the course itself including its assessment regime. It then presents the costs and risks associated with such alignment, based upon my own experiences and drawing from input from the students. The report closes with suggestions on how to simplify the course structure while continuing to endeavor toward alignment.